PERAN GURU DALAM LAYANAN BIMBINGAN BELAJAR KELOMPOK UNTUK MENINGKATKAN KERJASAMA DAN KEPERCAYAAN DIRI SISWA KELAS IV SD NEGERI BALFAI KABUPATEN KUPANG - Kiki Sopo; Silvester P Taneo; Maxsel Koro (Journal of Character and ELementary Education, 2023)
This study aims to describe the teacher's role in group tutoring services to increase the cooperation and self-confidence of fourth-grade students at SD Negeri Balfai, Kupang Regency. This type of research uses descriptive qualitative research. Data collection techniques used by researchers in this study are observation techniques, interview techniques, and documentation study techniques. The focus of the research in this study was the teachers and students of class IV which consisted of 25 students with 12 female students and 13 male students. Based on the results of this study, it can be concluded that the role of the teacher in group tutoring services to increase and self-confidence of fourth-grade students at SD Negeri Balfai Kupang Regency, is as follows. (1) The background for implementing group guidance is to guide students who lack self-confidence. (2) The forms of group guidance used to increase student cooperation and self-confidence are group activities and group discussions. (3) The contribution of group guidance made by the supervising teacher is directing students to continue to apply the values ​​taught by the teacher, not only in the learning process but also in collaborating in group guidance in class IV of SD Negeri Balfai Kupang Regency.